2014
DOI: 10.1128/jvi.03300-13
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of a Herpes Simplex Virus 1 dUTPase by a Viral Protein Kinase, Us3, Dictates Viral Pathogenicity in the Central Nervous System but Not at the Periphery

Abstract: Herpes simplex virus 1 (HSV-1) encodes Us3 protein kinase, which is critical for viral pathogenicity in both mouse peripheral sites (e.g., eyes and vaginas) and in the central nervous systems (CNS) of mice after intracranial and peripheral inoculations, respectively. Whereas some Us3 substrates involved in Us3 pathogenicity in peripheral sites have been reported, those involved in Us3 pathogenicity in the CNS remain to be identified. We recently reported that Us3 phosphorylated HSV-1 dUTPase (vdUTPase) at seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…We also showed that Us3 phosphorylation of vdUTPase at Ser-187 promoted viral replication in human neuroblastoma SK-N-SH cells but not in human carcinoma HEp-2 cells (21) and promoted viral pathogenicity in the CNS of mice but not at peripheral sites, including the eyes and vagina (22). These observations, together with the hypothetical role of dUTPases encoded by the various viruses described above, led us to hypothesize that (i) dUTPase activity was critical for efficient HSV-1 replication; (ii) Us3 phosphorylation of vdUTPase at Ser-187 upregulated its enzymatic activity to compensate for insufficient host cell dUTPase activity for efficient viral replication, such as in SK-N-SH cells; and (iii) this phosphorylation played no role in viral replication in cells with sufficient cellular dUTPase activity, such as HEp-2 cells.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…We also showed that Us3 phosphorylation of vdUTPase at Ser-187 promoted viral replication in human neuroblastoma SK-N-SH cells but not in human carcinoma HEp-2 cells (21) and promoted viral pathogenicity in the CNS of mice but not at peripheral sites, including the eyes and vagina (22). These observations, together with the hypothetical role of dUTPases encoded by the various viruses described above, led us to hypothesize that (i) dUTPase activity was critical for efficient HSV-1 replication; (ii) Us3 phosphorylation of vdUTPase at Ser-187 upregulated its enzymatic activity to compensate for insufficient host cell dUTPase activity for efficient viral replication, such as in SK-N-SH cells; and (iii) this phosphorylation played no role in viral replication in cells with sufficient cellular dUTPase activity, such as HEp-2 cells.…”
mentioning
confidence: 88%
“…We recently reported that Us3 phosphorylation of vdUTPase Ser-187 was required for efficient viral replication and virulence in the CNS of mice after intracranial inoculation, whereas it played no role in viral replication and pathogenicity in the eyes and vaginas of mice after ocular and vaginal inoculation, respectively (22). Therefore, these results in mice, like those in the present study with cultured cells, suggested that Us3 phosphorylation of vdUTPase Ser-187 is required to compensate for low cellular dUTPase activity to provide sufficient dUTPase for efficient viral replication in the CNS of mice, since epithelial cells in the eyes and vagina are actively dividing but most cells in the CNS are not (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that Us3, an HSV-1-encoded serine/threonine protein kinase, phosphorylated vdUTPase at serine 187 (Ser-187), which upregulated its enzymatic activity in HSV-1-infected cells (15). We also showed that this phosphorylation promoted viral replication in human neuroblastoma SK-N-SH cells and viral replication and virulence in the central nervous system (CNS) of mice (15,16). Thus, regulation of vdUTPase activity by Us3 phosphorylation of vdUTPase Ser-187 appeared to be important for HSV-1 replication and pathogenicity.…”
mentioning
confidence: 99%
“…These results suggested that Us3 phosphorylation of vdUTPase Ser-187 upregulated its enzymatic activity and that this upregulation compensated for low cellular dUTPase activity for efficient HSV-1 replication, at least in cell cultures. This also appeared to be the case in vivo, based on our previous report that Us3 phosphorylation of vdUTPase Ser-187 promoted viral replication and virulence in the CNS of mice, in which most cells are not dividing, but played no obvious role in viral replication and pathogenicity in the eyes and vaginas of mice, in which the HSV-1 target epithelial cells are actively dividing (16,23,24). However, experimental data to directly prove that the dUTPase of HSV-1 and other viruses is needed to compensate for insufficient cellular dUTPase activity for viral replication and pathogenicity in some cells in vivo have not been reported thus far.…”
mentioning
confidence: 99%
“…1). Replacement of the phosphorylation site with an acidic amino acid, such as glutamic acid or aspartic acid, is a phosphomimetic mutation (a mutation that mimics the negative charges produced by phosphorylation) (31)(32)(33). We first inquired whether phosphorylation of pUL12 Tyr-371 had an effect on UL12 expression in HSV-1-infected cells.…”
Section: Identification Of Tyr-371 As a Phosphorylation Site In Pul12mentioning
confidence: 99%